Comparative Histomorphological Study of Kidneys in Pigeon (Columba livia) and Starling Birds (Sturnus valguris) - Suhaib A. H. AL-Taai1 , Riyadh H. Nasif1 (Indian Journal of Forensic Medicine & Toxicology, 2020)
This paper is focused application on the histomorphological and morphometrical differences of the kidneysof two species (Sturnus valguris and Columba livia ) belong to different orders varied in climate. Our studyused 30 birds divided into two equal groups; first was 15 starling birds (Sturnus valguris) and the secondgroup consisted of 15 pigeon (Columba livia). The current study showed morphological results of kidneysin both birds, where appeared differences between kidneys. In starling’s kidney was described square shapewith fused left and right kidneys, either pigeon’s kidney was divided in to three lobes (cranial, middleand caudal) with elongated-like. The present study was revealed Mean measurements. The study recordedlength of starling’s kidney was (4.43±0.12cm), while weight and volume were recorded (3.75±0.05g) and(2.28m±0.04cm³) respectively, while in pigeon was kidney length (5.45±0.12cm), weight of kidney was(4.85±0.02g) and volume about (2.21±0.06cm³). Microscopic results were included in two species, the renalcortex which made up the majority of the kidney, while small region of kidney called medulla. Our studywas different impatience between starling’s bird and pigeon kidney about renal corpuscles, where the studyshowed the bowman’s space in starling bird was wide from pigeon. The study observed significant statisticsanalysis. Mean measurement was (10.64±0.02µm) and (8.65±0.04µm) in bowman’s space, while mean ofthe glomerulus capillaries and renal corpuscles of pigeon was a larger than starling’s bird (47.54±0.11µm),(26.60±0.12µm),(56.55±0.12µm) and (37.41±0.11µm) respectively. Also the present work was recordedsignificant statistics analysis during calculation the number of renal corpuscles in 1 mm² in starling birdkidney was more than that in the kidney of pigeon (20.25 ± 0.23µm) and (16.42 ± 0.01µm).